Formation of Methodical Approach to the Assessment of Coherence of Socio-economic Space of Agglomeration - Volchkova, Irina V.; Danilova, Maria N.; Podoprigora, Yulia V.; Ufimtseva, Evgeniya V.; Seliverstov, Alexey A.; Shadeyko, Nikolay R. (International Journal of Economics and Financial Issues, 2016)
The research context lays around the issues of coherence of socio-economic space of agglomerations in aspects of the balanced development of the country. The vector of the study is interfaced with the increasing course of Russian regions towards formation of agglomerations and with insufficient study of coherence of the properties of socio-economic space in this regard. Formation of methodical approach to the assessment of coherence of social and economic space in agglomerations makes the scientific and practical novelty of research. The paper is based on a case study of Tomsk agglomeration. The study concludes that coherence of socio-economic space acts as the defining factor of formation and development of agglomerative processes. Keywords: agglomeration, regional development, socio-economic space, coherence JEL Classifications: E2, R12, O11